The Enduring Enigma: Philosophical and Foundational Challenges to Infinity in Mathematics and Science - A Mageed, Ismail (Optimality, 2025)
For millennia, philosophers have been enthralled and bewildered by the concept of infinity, a cornerstone of contemporary mathematics and physics. Though its official inclusion into set theory and calculus has produced great explanatory power and predictive success, its ontological status and practical consequences continue to spark great philosophical and foundational arguments. Investigating past contradictions, competing mathematical ideas like finitism and constructivism, and the confusing part infinity plays in modern scientific theories, this essay looks at the persistent obstacles to the uncritical acceptance of infinity. It claims that, though useful, the idea of infinity is still an unanswered question, providing fertile ground for fresh scientific thought and possibly calling for a re-evaluation of its basic nature in describing reality.